2022
DOI: 10.3390/biom12020292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PD-L1 Expression in Undifferentiated Pleomorphic Sarcomas, Liposarcomas and Chondrosarcomas

Abstract: Immune checkpoint inhibitors (ICIs) such as PD1/PD-L1 blockers are an established treatment for many solid cancers. There are currently no approved ICIs for sarcomas, but satisfactory results have been seen in some patients with disseminated disease in certain histological types. Most studies on PD-L1 in sarcoma have used small specimens and there are no clear cutoff values for scoring. We investigated PD-L1 immunoreactivity in high-grade chondrosarcomas (CS), abdominal liposarcoma (LS) and undifferentiated pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The presence of tumor-infiltrating lymphocytes and PD-L1 expression are both generally promoted by anti PD-1/L1 blockade [ 10 ]. However, Zhang et al found no significant difference in metastasis-free or overall survival in cases of liposarcoma, regardless of PD-L1 expression [ 11 ]. The effectiveness of immune checkpoint blockade therapy has recently been investigated in an open-label phase II study of anti-PD-1 monotherapy in patients with histological evidence of metastatic or surgically unresectable locally advanced sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of tumor-infiltrating lymphocytes and PD-L1 expression are both generally promoted by anti PD-1/L1 blockade [ 10 ]. However, Zhang et al found no significant difference in metastasis-free or overall survival in cases of liposarcoma, regardless of PD-L1 expression [ 11 ]. The effectiveness of immune checkpoint blockade therapy has recently been investigated in an open-label phase II study of anti-PD-1 monotherapy in patients with histological evidence of metastatic or surgically unresectable locally advanced sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…STS is generally described as having low PD-L1 expression with response rates range 5%-18% (11,38). Sarcomas with PD-L1 expression include angiosarcoma, chondrosarcoma, Ewing's sarcoma, rhabdomyosarcoma, synovial sarcoma, and UPS, among which high PD-L1 expression tends to be more common in UPS (8,34). Zhang et al (8), used the SP263 assay to measure PD-L1 expression in chondrosarcoma, liposarcoma, and UPS, respectively, and observed increased response rates in the UPS group, with TPS >50% observed in 8 tumors (8/96).…”
Section: Discussionmentioning
confidence: 99%
“…STS is generally described as having low PD-L1 expression with response rates range 5%-18% ( 11 , 38 ). Sarcomas with PD-L1 expression include angiosarcoma, chondrosarcoma, Ewing’s sarcoma, rhabdomyosarcoma, synovial sarcoma, and UPS, among which high PD-L1 expression tends to be more common in UPS ( 8 , 34 ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations